Association of ferritin autoantibodies with giant cell arteritis/polymyalgia rheumatica. Issue 6 (5th January 2012) - Baerlecken, N T; Linnemann, A; Gross, W L; Moosig, F; Vazquez-Rodriguez, T R; Gonzalez-Gay, M A; Martin, J; Kötter, I; Henes, J C; Melchers, I; Vaith, P; Schmidt, R E; et al.
Abstract : Objectives: Polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) are relatively common inflammatory disorders. Establishing the diagnosis however may be difficult, since so far no specific biomarkers of the disorders are available. Methods: As a screening procedure, the authors used protein arrays for the detection of new autoantigens in GCA and PMR. The results of the protein array were confirmed by different ELISAs detecting IgG antibodies against the human ferritin heavy chain, N-terminal 27 amino acids of the human ferritin heavy chain or the homologous peptide of Staphylococcus epidermidis . Sera of patients with only GCA (n=64), only PMR (n=47) and both PMR and GCA (n=31) were used. Results: In the ELISA using the human ferritin peptide, the sensitivity of IgG antibodies against ferritin was 92% in 36 GCA and/or PMR patients before initiation of treatment, 22/32 (69%) in patients with disease flares and 64/117 (55%) in the total cohort including treated and inactive patients. In controls, the false positive rate was 11/38 (29%) in systemic lupus erythematosus, 1/36 (3%) in rheumatoid arthritis, 0/31 (0%) in late onset rheumatoid arthritis, 3/46 (6.5%) in B-non-Hodgkin's lymphoma and 1/100 (1%) in blood donors. In the ELISA using the ferritin peptide of S epidermidis, 89% of 27 patients with untreated GCA and PMR were positive. Conclusion: Antibodies against the ferritin peptide were present in up to 92% of untreated, active GCA and PMR patients. They can be useful as a diagnostic marker of PMR and GCA.